Are we overestimating proton minibeam therapy effectiveness through physical dose metrics? - Dere, Kaan; Usta, Ahmet Cemal; Kurnaz, Reyhan Serra; Lin, Liyong; Yang, Yong; Surucu, Murat; Charyyev, Serdar (Frontiers in Oncology, 2025)
PurposeThe conventional implementation of proton spatially fractionated radiotherapy (SFRT) uses physical collimators with millimeter apertures to generate minibeams, creating alternating regions of high-dose peaks and low-dose valleys. Current evaluation of SFRT effectiveness predominantly relies on physical quantities, particularly the peak-to-valley dose ratio (PVDR). While high PVDR and low valley doses have been correlated with improved normal tissue sparing, this physical metric-based approach provides an incomplete picture of the treatment’s biological impact. In this work, we aim to quantify biological dose for proton minibeams created using physical collimators and critically evaluate the adequacy of physical (PVDRPHYS) as compared to biologically weighted PVDR (PVDRBIOL).MethodsMonte Carlo simulations using TOPAS were performed to model proton minibeam arrangements with 70 and 150 MeV monoenergetic beams, as well as a Spread-Out Bragg Peak (SOBP) configuration to represent clinically relevant dose delivery. We investigated the impact of multiple collimator configurations on PVDR: collimator thickness (6.35 cm), hole diameter (1–3 mm), center-to-center (c-t-c) distances (2, 3, 4 mm for 1 mm hole, 4, 6, 8 mm for 2 mm hole) and air gaps (5, 10, and 15 cm) between the collimator and water phantom. For each configuration, 3D dose and dose-averaged LET (LETd) distributions were scored in water phantom, which were subsequently used for RBE calculation using the McNamara model with α/β ratios of 3 or 10 Gy.ResultsOur comprehensive analysis revealed significant differences between physical and biological PVDR metrics across various configurations. For both 70 and 150 MeV beams, PVDRBIOL was consistently lower than PVDRPHYS by 1-25% and 1-21%, respectively, with the most pronounced differences observed at shallow depths, smaller air gaps with larger hole diameter and c-t-c distances. Similar reductions (3.9%-26.5%) in PVDRBIOL were observed for the SOBP configuration, with the specific pattern depending on the energy composition and weighting of constituent layers.ConclusionsThe significant variations between PVDRPHYS and PVDRBIOL across different beam energies, depths, and collimator configurations demonstrate that conventional PVDR calculations based solely on physical dose may not fully represent the biological impact of proton SFRT. These findings highlight the importance of incorporating radiobiological considerations when evaluating and optimizing proton minibeam therapy, potentially leading to more biologically informed treatment planning approaches.